Decimal Selection Functions. Issue 7 (9th August 2019) - Maltenfort, Michael
Abstract: When we take a decimal form of a number in the unit interval [ 0, 1 ], we can form a new number by selecting certain digits and discarding the others. We analyze the properties of this process, particularly in relationship to a recentMonthly article.